Aerobic capacity of elite soccer players - Suzic, J.; Mazic, S.; Ostojic, S.; Dikic, N.; Mitrovic, D. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
It is well known that good aerobic capacity, specially in soccer, is one of the best predictor for success (Apor, 1988). The aim of this study was to determine the aerobic capacity of Serbian professional club soccer players, variations associated with the positional role and to make comparison with European top leagues counterparts. Methodology 31 male soccer player (age 25.2 ± 4.2) performed an incremental ramp protocol on treadmill at the beginning of a preparation period. Maximal oxygen consumption (VO2 max) and HR were measured directly (Jaeger Oxycon pro). Results The highest mean estimated VO2 max values had midfield players (53.3±1.9 ml.kg-1.min-1) than forwards (52.9±4.4 ml.kg-1.min-1), defenders (51.8±3.3 ml.kg-1.min-1) and goalkeepers (50.5±1.8 ml.kg-1.min-1). No statistical differences were found in VO2 max between players on different positions, except between goalkeepers and midfield players (P< 0.05). Comparing with results reported from other European soccer teams (Reilly, Bagsbo, Franks, 2000), it was found that Serbian players had lower mean VO2 max within each positional group (P<0.01) except goalkeepers. No difference was found (P>0.05) in running economy between players at the various treadmill velocities. Discussion/Conclusion The small difference in inter-player VO2 max values most likely reflects lower-quality training programs. That could also be an explanation for large differences in mean VO2 max between our players and European counterparts. Relatively lower results of Serbian players lead us to conclusion that there is a great importance of improving and designing optimal position-specific training, especially with young categories. That could be a necessary step to achieve the best performance.